Proceedings of the 3rd International Conference of Business, Accounting, and Economics, ICBAE 2022, 10-11 August 2022, Purwoker 2022
DOI: 10.4108/eai.10-8-2022.2320779
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Islamic Leadership, Work Stress, Compensation, Promotion And Motivation On Employee Performance

Abstract: This study aims to examine the effect of Islamic leadership, work stress, compensation, promotion and motivation on employee performance at Muhammadiyah Siti Aminah Bumiayu Hospital. This type of research is quantitative research with primary data sources obtained from questionnaires. Data collection through questionnaires produces structured data so that researchers can carry out the process of quantifying data, namely changing the original data into numbers. The population of this study were all employees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This investigation result does not match with research of (Hassan et al, 2020;Mulyana et al, 2021b) which concluded that motivation did not have a significant effect on employee performance. However, the study result is in line with the study conducted by (Sudiardhita Ketut IR et al, 2018) and research conducted by (Gunawan et al, 2022;Syamsul et al, 2019) asserted that motivation positively and significantly affects employee performance. Individuals are motivated by a hierarchy of needs, which goes from basic physiological demands to higher-level needs like self-actualization, according to Maslow's theory of the hierarchy of needs.…”
Section: T-testsupporting
confidence: 90%
See 4 more Smart Citations
“…This investigation result does not match with research of (Hassan et al, 2020;Mulyana et al, 2021b) which concluded that motivation did not have a significant effect on employee performance. However, the study result is in line with the study conducted by (Sudiardhita Ketut IR et al, 2018) and research conducted by (Gunawan et al, 2022;Syamsul et al, 2019) asserted that motivation positively and significantly affects employee performance. Individuals are motivated by a hierarchy of needs, which goes from basic physiological demands to higher-level needs like self-actualization, according to Maslow's theory of the hierarchy of needs.…”
Section: T-testsupporting
confidence: 90%
“…Convenience sampling was the approach used for data sampling. According to (Gunawan et al, 2022)Convenience sampling is the process of selecting a sample based on a researcher's chance encounter with a responder who is willing to participate in research and is a member of the population.…”
Section: Research and Methodologymentioning
confidence: 99%
See 3 more Smart Citations